2014
DOI: 10.1128/jvi.01277-14
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Novel Alphaherpesvirus in Fruit Bats

Abstract: Bats are known to harbor emerging RNA viruses. Recent studies have used high-throughput sequencing technology to identify various virus species, including DNA viruses that are harbored by bats; however, little is known about the nature of these potentially novel viruses. Here, we report the characterization of a novel herpesvirus isolated from an Indonesian pteropodid bat. The virus, tentatively named fruit bat alphaherpesvirus 1 (FBAHV1), has a double-stranded DNA genome of 149,459 bp. The phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 39 publications
0
39
0
2
Order By: Relevance
“…No alphaherpesviruses were detected in this study nor in the study by Wibbelt et al [7] who analyzed bat lung tissues. However, evidence of alphaherpesviruses in other bats has recently been provided from spleen tissues of Indonesian fruitbats [5], and from throat swabs and salivary glands of other fruit bats from the genera Eidolon and Pteropus [6]. The absence of alphaherpesviruses in bats aside from fruit bats could indicate that bat alphaherpesviruses evolved only in the Pteropodidae family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No alphaherpesviruses were detected in this study nor in the study by Wibbelt et al [7] who analyzed bat lung tissues. However, evidence of alphaherpesviruses in other bats has recently been provided from spleen tissues of Indonesian fruitbats [5], and from throat swabs and salivary glands of other fruit bats from the genera Eidolon and Pteropus [6]. The absence of alphaherpesviruses in bats aside from fruit bats could indicate that bat alphaherpesviruses evolved only in the Pteropodidae family.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of alphaherpesviruses has recently been found in pteropid bats such as Eidolon helvum , E . dupreanum , Pteropus lylei (a nectarivorous bat), Lonchophylla thomasi , and an unidentified bat [5, 6]. Several betaherpesviruses and gammaherpesviruses have also been detected in bats from the families Vespertilionidae [7,8], Miniopteridae [9, 10], Pteropodidae [11], Hipposideridae [12] and Rhinolophidae [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed an ancient phylogenetic relationship between bats and a suite of other viral pathogens: in addition to lyssaviruses and henipaviruses, bats are now posited as the most ancestral host taxon for the entire family of paramyxoviruses (of which henipaviruses represent one genus [9]), as well as for CoVs [10], hepadnaviruses related to human hepatitis B virus [11], and hepaciviruses related to hepatitis C virus [12]. Bats also demonstrate deep phylogenetic relationships with influenza A virus [13], filoviruses [14], and simplex viruses [15]. Several authors have compiled informative reviews [16][17][18] and meta-analyses [19,20] from various perspectives, continually asking 'Are bats special in their reservoir roles for zoonotic pathogens?'…”
Section: Bats As Special Reservoirs For Viral Pathogensmentioning
confidence: 99%
“…The prevalence of HVs of the three subfamilies in many bat species was found in previous studies to be high [7][8][9][10][11]. Eight bat species, with prevalence rates of 3.47-33.33 %, were sampled from four areas of southern China in this study.…”
mentioning
confidence: 95%
“…In 2007, Wibbelt and co-workers first confirmed the presence of HVs in bats [7]. Recently, several studies have documented the high prevalence of HVs with diverse genetic characteristics in bats originating from the Philippines, Madagascar, Cambodia, Indonesia, Japan, Germany, and Hungary [8][9][10][11][12]. In 2012, four new HVs, two betaherpesviruses and two gammaherpesviruses, were identified in bats in China, using sequence-independent PCR amplification and next-generation sequencing technology, targeting the concatenated glycoprotein B (gB) and DNA-directed DNA polymerase (DPOL) genes of HVs [13].…”
mentioning
confidence: 99%